2011
DOI: 10.1097/jom.0b013e31823c1402
|View full text |Cite
|
Sign up to set email alerts
|

Time Spent in Physical Activity and Sedentary Behaviors on the Working Day

Abstract: Those employed in sedentary occupations were sedentary for approximately 11 hours per day, leaving little time to achieve recommended levels of physical activity for overall health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 23 publications
(24 reference statements)
4
73
3
Order By: Relevance
“…Our findings are not in line with two other studies [33, 34] that reported no differences in leisure time sitting between workers with sedentary jobs (‘white collar workers’) and workers with less sedentary jobs (‘blue collar workers’) on working days. Tudor-Locke et al [35] even reported opposite results compared to the results of the current study; i.e. workers in higher level of intensity-defined occupations spend more time on sedentary behaviors outside of work than workers in sedentary occupations.…”
Section: Discussioncontrasting
confidence: 97%
“…Our findings are not in line with two other studies [33, 34] that reported no differences in leisure time sitting between workers with sedentary jobs (‘white collar workers’) and workers with less sedentary jobs (‘blue collar workers’) on working days. Tudor-Locke et al [35] even reported opposite results compared to the results of the current study; i.e. workers in higher level of intensity-defined occupations spend more time on sedentary behaviors outside of work than workers in sedentary occupations.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, no research has taken into account hours worked in the labor market or occupational activity level when characterizing patterns of non-labor market time use, despite previous work showing that both employment status and occupational physical activity affect levels of sedentary activity and exercise during non-labor market hours (28; 31) . It is especially important to understand the relationship between non-labor market time use and physical activity among those who spend ≥40 h/week in the labor market (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially important to understand the relationship between non-labor market time use and physical activity among those who spend ≥40 h/week in the labor market (i.e. “full-time employees”), as these individuals face the highest time constraints on non-labor market time: on working days, 32% of time is spent on sleep and 31% is spent on labor market work, leaving little time to meet physical activity recommendations (28) . Even more important is identifying patterns of non-labor market time use among full-time employees in sedentary occupations, given that the majority of US employees are employed in sedentary jobs (32) , occupational physical activity is declining across the globe (4; 33) , and occupational inactivity has been linked to myriad adverse health consequences, including obesity, diabetes, cardiovascular disease, and mortality (32; 3437) .…”
Section: Introductionmentioning
confidence: 99%
“…Time use has been used as an indicator of occupational balance (Tudor-Locke, Leonardi, Johnson & Katzmarzyk, 2011;Wagman, Hakansson & Bjorklund., 2012), and time pressure can lead to potential loss in our occupational lives (Tranter, 2013).…”
Section: Temporal Dimensions Of Doing Being and Becoming: Clock Timementioning
confidence: 99%